EKSPLORASI PENGGUNAAN PLATFORM PEMBELAJARAN ONLINE GOOGLE CLASSROOM DALAM MATA PELAJARAN EKONOMI - Oktavia Indriyani (FKIP Unswagati, 2025)
This study identifies the benefits, challenges and opportunities of using google classroom online learning platform in supporting more effective and relevant economic learning. This research provides valuable insights for teachers, policy making, and educational technology development. This research uses qualitative method with the subjects of this research are teachers and students. The results show that Google Classroom provides significant benefits in the efficiency of learning management, especially to support online teacher and student activities. The main challenges found in this study were technical constraints such as limited internet access in certain areas affecting the smoothness of learning and the lack of direct interaction and classroom dynamics making them less motivated and lacking interest in learning. The learning becomes less interactive or only focuses on giving homework. Adequate infrastructure support and technology training for teachers and students are essential to overcome these obstacles. Google Classroom offers a great opportunity to develop project-based Economics learning methods, real-time discussions, and analysis of global issues. By optimally utilizing interactive features, this platform can support learning that is more critical, collaborative and relevant to the needs of the digital era. Therefore, utilizing Google Classroom in Economics learning is not only a technical solution, but also paves the way for more modern and effective learning innovations. Keywords: Google Classroom, Economics Learning, Online Learning, Learning Effectiveness,